2006
DOI: 10.1021/ja060529h
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of Protected Arylglycines by Rhodium-Catalyzed Addition of Arylboronic Acids to N-tert-Butanesulfinyl Imino Esters

Abstract: A new method for the Rh(I)-catalyzed addition of arylboronic acids to N-tert-butanesulfinyl imino esters has been developed for the asymmetric synthesis of arylglycine derivatives. This method provides high yields (61-90%) and diastereoselectivities (>98:2) for a variety of functionalized arylboronic acids. The N-sulfinyl arylglycine ester products are versatile intermediates for further transformations, including selective protecting group removal, conversion to beta-amino alcohols, and direct incorporation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
41
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(45 citation statements)
references
References 17 publications
1
41
0
3
Order By: Relevance
“…First, the Ntert-butanesulfinyl group was transformed to get the chiral acetylamines according to the standard procedure (Scheme 3, Method A). [19] When using the diastereomers 6aa and 6aa' under the same conditions, the corresponding products were obtained with 67% and 73% ee, respectively. From these results, we doubted that a certain racemization might occur in the desulfination and acetylation steps.…”
Section: Introductionmentioning
confidence: 96%
“…First, the Ntert-butanesulfinyl group was transformed to get the chiral acetylamines according to the standard procedure (Scheme 3, Method A). [19] When using the diastereomers 6aa and 6aa' under the same conditions, the corresponding products were obtained with 67% and 73% ee, respectively. From these results, we doubted that a certain racemization might occur in the desulfination and acetylation steps.…”
Section: Introductionmentioning
confidence: 96%
“…3 The addition of a variety of organometallic reagents proceeds with high diastereoselectivities, including lithium, 4 magnesium, 5 indium, 6 and zinc 7 reagents, and through the use of transition metal-catalysts, also organoboron reagents. 8 Transition metal catalysts have also been applied to the addition of allyl alcohols via isomerization pathways 9 and for the hydrogen-mediated reductive coupling of alkynes. 10 Stabilized anions such as enolates 11 and nitronate 12 anions also have been added with good selectivities.…”
Section: Introductionmentioning
confidence: 99%
“…5 Miyaura also reported rhodium-catalyzed additions of arylboronic acids to aldehydes and imines. 6 Recently, rhodium-catalyzed addition of aryland alkenylboronic acids to isocyanates 7 and enantioselective additions of arylboronic acids to aliphatic imines, 8 N-Boc imines 9 and N-tert-butanesulfinyl imino esters 10 have been reported. Palladium-catalyzed addition reactions of arylborons were reported by Uemura, who demonstrated that palladium catalyzes the conjugate addition to a,b-unsaturated carbonyl compounds.…”
Section: Introductionmentioning
confidence: 99%